2013
DOI: 10.1021/cs300785r
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Transfer Hydrogenolysis of Primary, Secondary, and Tertiary Benzylic Alcohols by Formic Acid: A Mechanistic Study

Abstract: A palladium-catalyzed transfer hydrogenolysis of primary, secondary, and tertiary benzylic alcohols by formic acid has been developed and studied. The product hydrocarbons were obtained in excellent yields from both secondary and tertiary benzylic alcohols and in good yields for primary benzylic alcohols. The rate of disappearance of 1-phenylethanol (1) follows zero-order dependence in 1 and first-order dependence in formic acid and palladium. Catalytic amounts of base inhibit a competing disproportionation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 38 publications
4
63
0
1
Order By: Relevance
“…The conversion followed a linear relationship with the catalyst amount in range 0-150 mg. The first-order dependence of the catalyst is clearly observed from the plot, which has been widely reported for other transfer hydrogenation processes [41,42]. Phenol conversion increased to 90% with catalyst amount of 150 mg, and the selectivity to cyclohexanone was 95%.…”
Section: Hydrogen Transfer With Formic Acidsupporting
confidence: 67%
See 1 more Smart Citation
“…The conversion followed a linear relationship with the catalyst amount in range 0-150 mg. The first-order dependence of the catalyst is clearly observed from the plot, which has been widely reported for other transfer hydrogenation processes [41,42]. Phenol conversion increased to 90% with catalyst amount of 150 mg, and the selectivity to cyclohexanone was 95%.…”
Section: Hydrogen Transfer With Formic Acidsupporting
confidence: 67%
“…Interestingly, regardless of the amount (5 mmol or 21 mmol) or groups of reductants (HCOOH, HCOONa, or H 2 ), similar activities were observed under identical conditions in initial period. Previous studies have suggested that the rate-determining step of transfer hydrogenation is the hydride transfer on Pd surface [42]. Therefore this result may also indicate that the H-H and C H (H COO − ) dissociation are both very fast on Pd/AC catalyst.…”
Section: Kinetics Of Transfer Hydrogenation On Pd/acmentioning
confidence: 74%
“…Nagaraja et al[10] and Sawadjoon et al[56] reached a similar conclusion in their analysis of the gas phase coupling of cyclohexanol dehydrogenation with furfural hydrogenation (T = 453-523 K, P = 1 atm) over Cu-MgO-Cr 2 O 3 and liquid phase coupling of alcohol hydrogenolysis with formic acid as hydrogen donor (T = 353 K, P = 1 atm) over Pd/carbon, respectively. Moreover, there is evidence in the literature for the formation of transitory metal-H (Cu-H[57], Ru-H[58], Ag-H[59] and Ni-H[60]) species (via interaction with hydrogen abstracted from alcohols) that can serve as a source of reactive hydrogen.…”
mentioning
confidence: 63%
“…They also tested other heterogeneous catalysts (Ir/C, Ni/C, Pd/C, Re/C, Rh/C) and Pd/C showed the higher reactivity in the cleavage of the β-O-4 C-O bond, allowing an efficient transformation to the corresponding aryl ketones and phenols in high yield, at 80 • C for 1-24 h. They proposed a reaction mechanism in which the first key step is the dehydrogenation of the α-CHO group followed by formation of a Pd-enolate complex, that undergoes a transfer hydrogenolysis process [119,120].…”
Section: Cth Of Lignin Derived Moleculesmentioning
confidence: 99%